Analisis Pengaruh Infiltrasi Hujan Terhadap Stabilitas Lereng STA 62+450 S/D 62+825 Jalan Tol Seksi Sp. Indralaya – Prabumulih Dengan Software Geo Studio - Oktaliyani, Tiara; Soemitro, Ria Asih Aryani; Satrya, Trihanyndio Rendy (Kadiri University, 2024)
The construction of the Indralaya-Muara Enim Interchange Toll Road, especially the Indralaya-Prabumulih Interchange Section, was hampered by landslides after excavation was carried out between STA 62+450 to 62+825. The combination of steep slopes and rain infiltration weakened the soil structure, increasing the risk of landslidesThis research aims to analyze the effect of rainwater infiltration on slope stability on the Sp Section Toll Road Project. Indralaya–Prabumulih. The research methodology used was to analyze landslide slope areas using the Slope/W and Seep/W programs from Geo Studio. This study evaluated different excavation heights and an initial excavation slope of 1:3. The focus is on calculating the safety factor (SF) at varying rain durations (1 hour, 3 hours, and 5 hours), with SF values below 1.5 indicating instability. The Safety Factor (SF) value of the existing soil before excavation was 1.58, but after 1 hour of rain, the SF decreased to 1.33 (15.66% decrease). After 3 hours, SF dropped to 1.13 (28.34% decrease), and reached 1.10 (30.24% decrease) after 5 hours. Strengthening slopes using the Hydroseeding method increases SF to 1.83, while the use of Retaining Wall increases SF more significantly to 2.54. This research reveals the impact of rain infiltration on soil stability and proves the effectiveness of slope strengthening methods. These results are an important basis for planning effective landslide mitigation on toll road excavations.